Industrial Development Strategy and Stimulator Industry of Iran’s Economy - Bidabad, Bijan (International Journal of Business and Management Future, 2019)
With a glance on planning methodology, we try to analyze “Iran’s industrial development strategy proposition”. This proposition to somehow covers the requirements of Iran’s economic development strategy, and in this regard can be treated as an economic strategy plan and not industrial strategy plan. Approaches of this proposition-ignoring its long-run quantitative forecasts- can be used as a general solution to Iran’s long-run structural problems and can be summarized by international linkages and competitiveness as the main proposed strategies. But this proposition does not introduce stimulator engine sector of the economy; in this paper, we try to touch this nomination via an input-output sectoral linkages framework. We conclude that, to start of Iran’s economic fast growth, sectors of glass and glassware, cement, mine, other mineral & non-ferrous products, basic steel and iron mill products, paper & wood industries, chemical & plastic industries, copper & copper products, water and electricity in turn should be activated more to fulfill the needs for intermediate products in the economy. The sectors of foodstuff industries, aluminum, and other basic products of non-ferrous metals, copper and copper products, steel and iron mill products are able to increase the demand for intermediate products of other sectors more than the others. Basic steel and steel mill products, copper and copper products, aluminum and other basic non-ferrous metals products, cement, paper, and wood industries, glass and glassware, other mineral non-ferrous products, chemical industries, and plastic are more integrated than the others relating both forward and backward linkages. Machinery and equipment, basic products of steel and iron mill, chemical industries and plastic are mainly based on import and share of intermediate import to production of aluminum sectors and other basic products of non-ferrous metals, chemical industries, and plastic, basic steel and iron mill products, machinery and equipment industries is more than the other sectors. Aluminum and other basic products of non-ferrous metals, foodstuffs industries, basic products of steel and steel mill have a higher multiplier effect in increasing economy income, in other words, it is possible to consider them as pioneer sectors and economy stimulator engine. Aluminum and other basic products of non-ferrous metals, foodstuff industries, basic products of steel and iron mill have more affect the growth of other sectors. Sectors of chemical and plastic industries, agriculture, transportation services, warehouse keeping and communications, commercial services provide the highest amount of input for other sectors. We consider two scenarios for Iran’s industrial strategy as foodstuffs industries sector with export promotion, and the second, metals sectors (aluminum and other basic products of non-ferrous metals, basic products of steel and iron mill) with export promotion and import substitution.